Does preserved kidney volume predict 1 year donor renal function after laparoscopic living donor nephrectomy?. (17th January 2013) - Yakoubi, Rachid; Autorino, Riccardo; Kassab, Ahmad; Long, Jean Alexandre; Haber, Georges‐Pascal; Kaouk, Jihad H
Abstract: The aim of the present study was to evaluate whether preserved kidney volume predicts donor renal function at 1‐year post‐surgery. Data of patients who underwent laparoscopic living donor nephrectomy between October 2006 and September 2010 were retrospectively reviewed. All patients underwent computed tomography scan with an estimation of kidney volume by using an automated segmentation algorithm. We also calculated kidney volume adjusted for donor body surface area and donor preserved kidney volume ratio (split volume). Estimated glomerular filtration rate was estimated using the Modification of Diet in Renal Disease equation. Predictors of the estimated glomerular filtration rate at 1 year were assessed by multiple linear regression. The 1‐year estimated glomerular filtration rate was available in 140 patients. The median age was 40 years, and median adjusted preserved kidney volume was 160.5 cc/1.73 m 2 (interquartile range 143.7–177.9). Median estimated glomerular filtration rate was 92.4 (interquartile range 81.9–101.2) and 61.2 mL/min/1.73 m 2 (interquartile range 53.4–68.7), respectively, at baseline and at 1 year. Preserved kidney volume adjusted to body surface area ( P  = 0.02) with age ( P  = 0.002) and preoperative estimated glomerular filtration rate ( P  < 0.001) were independent predictors of estimated glomerular filtration rate at 1 year. However, split kidney volume was not statistically related to estimated glomerular filtration rate at 1 year ( P  = 0.47). In order to maximize preservation of donor renal function, the pre‐donation kidney volume adjusted to body surface area might be a useful parameter to consider when deciding on living kidney donation.